Molecular Imaging for the diagnosis of infective endocarditis: A systematic literature review and meta-analysis. (15th February 2018) - Juneau, Daniel; Golfam, Mohammad; Hazra, Samir; Erthal, Fernanda; Zuckier, Lionel S.; Bernick, Jordan; Wells, George A.; Beanlands, Rob S.B.; Chow, Benjamin J.W.
Abstract: Background: Infective endocarditis (IE) is a serious, potentially life-threatening condition. Currently, the modified Duke criteria is used to assist with the diagnosis of IE, but it can still remain difficult. Growing data supports the potential use of molecular imaging to assist in the diagnosis of IE. Our objective was to understand the potential utility of 18 F-fluorodeoxyglucose ( 18 F-FDG) positron emission tomography-computed tomography (PET-CT), 67 Ga citrate and radiolabeled white blood cell (WBC) scintigraphy in the diagnosis of IE. Methods and results: A systematic review of the literature and meta-analysis on the use of all 3 modalities in IE was conducted. The literature search identified 2753 articles. A total of 14 studies met the inclusion criteria (10 for 18 F-FDG, 3 for WBC and 1 for both modalities). No 67 Ga citrate study met the inclusion criteria. Pooled sensitivity of 18 F-FDG studies with adequate cardiac preparation for the diagnosis of IE was 81% (95% CI, 73%–86%) and pooled specificity was 85% (95% CI, 78%–91%). There was good overall accuracy with an area under the curve (AUC) of 0.897. Pooled sensitivity of WBC for the diagnosis of IE was 86% (95% CI, 77%–92%) and pooled specificity was 97% (95% CI, 92%–99%). The overall accuracy of WBC was excellent with an AUC of 0.957. Conclusions: Both 18 F-FDG and WBC have good sensitivity, specificity and accuracy for the diagnosis of IE. Both modalities are useful in the investigation of IE, and should be considered in cases where the diagnosis is uncertain.